Strategi Mengatasi Aksesibilitas Destinasi Pulau Kecil Dengan Penyesuaian Segmentasi Wisatawan Kepulauan Riau - Narotama, Mohammad Rachmadian; Saduddin, Saduddin; Furjatullah, Sarah Auliya (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2023)
A prevalent challenge encountered by small islands pertains to accessibility. Nevertheless, numerous ostensibly isolated islands attract a substantial number of tourists. This article examines the relationship between accessibility and tourism development on small islands to understand the two better. Qualitative data collection methods were utilized for this study, including in-depth interviews, the collection of pertinent secondary data, and field observations. Following analysis, the collected data were presented in a comparative descriptive fashion. A discussion of the island approach (islands and archipelagos) is undertaken to comprehend the interconnections between minor islands and other locations within the larger region. Field research indicates that despite possessing the aesthetic appeal of beaches and sea, many small islands still need to exploit their tourism potential fully. This is primarily due to the exorbitant transportation expenses for domestic visitors and the need for adequate tourism infrastructure, including resorts and hotels of international caliber catering to affluent-class tourists (middle and above). Conversely, despite being classified as remote islands, the Riau Archipelago maintains strong diplomatic relations with neighboring nations. It can attract international visitors for cultural tourism, beach activities, and scuba diving. Small islands may benefit from a strategy targeting affluent classes and foreign tourists. In order to develop the tourist experience on small islands by expectations, it is necessary to enhance tourism infrastructure and services for tourists and tourism investors as a result of targeting the tourist segment.